Climatology of extreme cold events in the central Peruvian Andes during austral summer: origin, types and teleconnections - Sulca, Juan (2018)
The climatological and large-scale characteristics of the extreme cold events (ECEs) in the central Peruvian Andes (Mantaro basin (MB)) during austral summer (January–March) are examined using reanalysis, gridded and in situ surface minimum temperature (Tmin) data for the 1979–2010 period.